Assessment of soil organic carbon fractions under sugarcane harvest residue management - Ararat-Orozco, Milton Cesar; Muñoz-Arboleda, Fernando; Sanclemente-Reyes, Oscar Eduardo (Revista de Ciencias Agrícolas, 2025)
Labile carbon (LC), measured by Permanganate oxidizable Carbon (POXC) techniques, and mineralizable carbon (MC), assessed through microbial CO₂ flux, are soil organic carbon (SOC) fractions that serve as sensitive indicators of soil management practices and soil organic matter (SOM) composition. Thus, this type of study is necessary for managing soil fertility in sugarcane cultivation systems. The experiment was based on measuring SOC fractions with different percentages of crop residue removal (T1:0%, T2:20%, T3:40%, T4:60%, T5:80%, and T6:100%) in a Pachic Vertic Haplustolls soil whose plots had the crop variety CC 93 4418. The experimental design was Randomized Complete Blocks. Samples were collected at three depths during the seventh ratoon. The plant biomass variables were expressed in tons per hectare. The effects of treatments on LC and MC were compared using analysis of variance (P-value of 0.05 or less), the Tukey test, a Pearson correlation analysis among soil properties, and a conceptual analysis between LC and MC was established through least squares linear regression. The LC across the three depths recorded significant differences, with T2 exhibiting the highest value of 328.91(mg. kg-1) and T6 exhibiting the lowest average of 272.75 (mg. kg-1). High correlations were observed between LC and soil properties such as CEC, volumetric water content, and gravimetric water content. Treatments could be directed towards high accumulation for T1 and T2 and high mineralization for T6 based on the correlation between LC and MC. Regarding the productivity parameter, T2 showed a higher TCH (211.66) with a more significant percentage change in LC increase over time. It is concluded that a soil without cover presents high CM dynamics but with low nutrient storage reflected in the CL.